2015 International Conference on Technologies for Sustainable Development (ICTSD) 2015
DOI: 10.1109/ictsd.2015.7095919
|View full text |Cite
|
Sign up to set email alerts
|

A review of emerging trends on water quality measurement sensors

Abstract: New concepts and techniques are replacing traditional methods of water quality parameters measurement systems. In modern sensor era, Optical Sensors (OS), Microelectronic Mechanical Systems (MEMS) and Bio-Sensors are important sensing techniques for different water quality parameter detection. Furthermore, these sensors are highly selective, sensitive, economical and user-friendly with quick response. This paper comprehensively reviews and discuss role of emerging techniques in detection of important water qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 56 publications
0
22
0
3
Order By: Relevance
“…Python has been experimented in a wide variety of applications ranging from environmental, home and industrial. Python framework has also been used in the development of ubiquitous wireless sensor network frameworks (Bocchino et al, 2015). Python facilitates the task of application development and minimizes the dependency on expertise of the embedded system.…”
Section: Cps Soft Computing Framework Developmentmentioning
confidence: 99%
“…Python has been experimented in a wide variety of applications ranging from environmental, home and industrial. Python framework has also been used in the development of ubiquitous wireless sensor network frameworks (Bocchino et al, 2015). Python facilitates the task of application development and minimizes the dependency on expertise of the embedded system.…”
Section: Cps Soft Computing Framework Developmentmentioning
confidence: 99%
“…Starting from the late 2000s, new technologies were introduced to address some of these limitations. In particular, new sensors were developed that utilize fiber optics, laser technology, biosensors, optical sensors, and microelectronic mechanical systems (MEMS) to detect different water quality parameters in situ [Bhardwaj et al 2015;Sawaya et al 2003], whereas computing and telemetry technologies were introduced to support the data acquisition and monitoring processes. Moreover, new methodologies like satellite image acquisition to remotely estimate some water quality parameters [Sawaya et al 2003] and architectures for visualizing the water quality parameters through the Internet were introduced to monitor lakes, rivers, and other water bodies [Hall et al 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally turbidity measurements have involved onsite water sample collection and subsequent laboratory analysis, which is both labour-intensive and costly [3]. Several studies have shown that the need for continuous online water quality monitoring has become essential to the water industry and for ecosystem research [4] [5]. These studies have also proven the need for high spatial and temporal resolution of the on-line monitoring systems in order to recover adequate data on which to base downstream control measures or ecosystem models or both.…”
Section: Introductionmentioning
confidence: 99%